Determinants of consumer confidence in emerging economies: a panel cointegration analysis - Çelik, Sadullah; Aslanoğlu, Erhan; Uzun, Seda (My University, 2010)
This study aims to analyze the relationship between consumer confidence and economic growth in six emerging economies, namely Brazil, China, Mexico, Poland, South Africa and Turkey. The relationship between consumer confidence and economic activity in developed markets has been well documented (Carroll et al., 1994, Howrey, 2001 and Ludvigson, 2004). However, to our knowledge, there are hardly any studies which assess the validity of this theoretical framework for households in emerging economies. We propose that there are two different variables that could play a significant role on consumer confidence in emerging economies as economic variables that measure production and financial variables that reflect the relationship between consumer confidence and financial markets. This study uses panel data analysis via conducting panel unit root and cointegration tests. Our empirical findings show that consumer confidence, industrial production and stock exchange have a long-run relationship in emerging economies. Moreover, households in emerging and developed markets exhibit similar behavior.
Keywords: Consumer Confidence, Emerging Markets, Financial Market Variables, Panel Cointegration.